Assessment of the virulence spectrum and its association with genetic diversity in Magnaporthe oryzae populations from sub-Saharan Africa - Mutiga, Samuel K.; Rotich, F.; Ganeshan, V.D.; Mwongera, D.T.; Mgonja, Emmanuel M.; Were, Vincent M.; Harvey, Jagger J.W.; Zhou, B.; Wasilwa, L.; Feng, C.; Ouédraogo, I.; Wang, G.L.; et al. (Scientific Societies, 2017)
A collection of 122 isolates of Magnaporthe oryzae, from nine sub-Saharan African countries, was assessed for virulence diversity and genetic relatedness. The virulence spectrum was assessed by pathotype analysis with a panel of 43 rice genotypes consisting of differential lines carrying 24 blast resistance genes (R-genes), contemporary African rice cultivars, and susceptible checks. The virulence spectrum among isolates ranged from 5 to 80%. Five isolates were avirulent to the entire rice panel, while two isolates were virulent to ∼75% of the panel. Overall, cultivar 75-1-127, the Pi9 R-gene donor, was resistant to all isolates (100%), followed by four African rice cultivars (AR105, NERICA 15, 96%; NERICA 4, 91%; and F6-36, 90%). Genetic relatedness of isolates was assessed by single nucleotide polymorphisms derived from genotyping-by-sequencing and by vegetative compatibility tests. Phylogenetic analysis of SNPs of a subset of isolates (n = 78) revealed seven distinct clades that differed in virulence. Principal component analysis showed isolates from East Africa were genetically distinct from those from West Africa. Vegetative compatibility tests of a subset of isolates (n = 65) showed no common groups among countries. This study shows that blast disease could be controlled by pyramiding of Pi9 together with other promising R-genes into rice cultivars that are adapted to East and West African regions.